Open/closed topological CP1 sigma model revisited - Elitzur, Shmuel; Walcher, Johannes (Journal of high energy physics, 2012)
We consider the topological sigma-model on Riemann surfaces with genus g and h holes, and target space CP1≅S2CP1≅S2 \mathbb{C}{\mathbb{P}^1} \cong {S^2} . We calculate the correlation functions of bulk and boundary operators, and study the symmetries of the model and its most general deformation. We study the open/closed topological field theory (TFT) correspondence by summing up the boundaries. We argue that this summation can be understood as a renormalization of the closed TFT. We couple the model to topological gravity and derive constitutive relations between the correlation functions of bulk and boundary operators.